Improving the Stability and Quality of Service in Cluster Head Rule Base System Using MANETs - Smita; Bhakar, Renu (International Journal of Computer Sciences and Engineering, 2014)
Abstract-This paper considers the problem of finding high and low frequency node disjoint and multi constrained QoS multipath from source to destination by using agent based fuzzy inference system. CGSR protocol divide the network into several small areas called clusters and the members of each cluster entrusted to a special node called cluster-head. A fuzzy logic system was proposed by which we select a suitable cluster-head to improve the quality of CGSR protocol. Selecting an appropriate cluster-head can save the power of overall network because the Cluster-Head node consumes more power than other ordinary nodes and the node with the highest chance is elected as the cluster-head. (1) Determination of multiple paths and picking up of resource information (available energy, mobility,distance,and chance) of the intermediate nodes from source to destination. (2) Recognition of node disjoint, and multi-constrained QoS fit paths by using Takagi-Sugeno Fuzzy Inference System (TSFIS). TSFIS extracts a fuzzy QoS weight from available resource information of the intermediate nodes. (3) Selection of the best path depending on the fuzzy QoS weight. (4) Maintenance of QoS path when path breaks due to mobility of node or link failure. To test the performance effectiveness of the approach. Simulation results show that our proposed protocol is better than I-MAN on the basis of data drop, load, delay and throughput parameters. Hence, the proposed system gives an efficient result in the presence and absence of threats because it launches an appropriate protocol on the basis of network contexts.